2013
DOI: 10.1172/jci63836
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 suppresses TβRII-mediated myofibroblastic activation and metastatic growth in liver

Abstract: In the tumor microenvironment, TGF-β induces transdifferentiation of quiescent pericytes and related stromal cells into myofibroblasts that promote tumor growth and metastasis. The mechanisms governing myofibroblastic activation remain poorly understood, and its role in the tumor microenvironment has not been explored. Here, we demonstrate that IQ motif containing GTPase activating protein 1 (IQGAP1) binds to TGF-β receptor II (TβRII) and suppresses TβRII-mediated signaling in pericytes to prevent myofibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(155 citation statements)
references
References 59 publications
4
150
1
Order By: Relevance
“…tor 1 to IQGAP1 (18). Similarly, VEGF enhances the interaction of vascular endothelial growth factor receptor-2 with IQGAP1 in human umbilical vein endothelial cells (19), and transforming growth factor ␤-1 (TGF-␤1) increases the binding of IQGAP1 to TGF-␤ receptor II (34). In contrast to these data, we observed that E 2 significantly attenuated the interaction between IQGAP1 and ER␣ in cells.…”
Section: Discussioncontrasting
confidence: 66%
“…tor 1 to IQGAP1 (18). Similarly, VEGF enhances the interaction of vascular endothelial growth factor receptor-2 with IQGAP1 in human umbilical vein endothelial cells (19), and transforming growth factor ␤-1 (TGF-␤1) increases the binding of IQGAP1 to TGF-␤ receptor II (34). In contrast to these data, we observed that E 2 significantly attenuated the interaction between IQGAP1 and ER␣ in cells.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, TP53, IKBKB, TGFB1 and TGFBR2 are strongly associated with EMT (p = 9.0 × 10 −6 , Fisher’s exact test). A literature search revealed that IQGAP1 has been shown to bind TGFBR2, following TGF-β stimulation, which promotes SMURF1 association with TGFBR2 and subsequent ubiquitination/degradation of the receptor (30). Additionally, dysregulated TGF-β signaling has been shown to be pro-oncogenic (31).…”
Section: Resultsmentioning
confidence: 99%
“…Biotinylation Assay for Plasma Membrane Integrin ActivityBiotin-based assays were performed as described previously (22,30). HSCs were fasted overnight and treated with exosome for 15 min.…”
Section: Methodsmentioning
confidence: 99%